Dimensional stability of cement paste and concrete subject to early-age carbonation curing - Xian, Xiangping; Logan, Chad; Shao, Yixin (Materials and structures, 2022)
Early-age carbonation curing of concrete is receiving more interest in terms of performance improvement and emission reduction. However, the volume change of cement-based products subject to carbonation curing may become a concern because of the potential carbonation shrinkage and its related shrinkage cracking. The purpose of this study was to investigate the dimensional stability of cement paste and concrete subject to the early-age carbonation curing. It was found that the carbonation curing introduced first an initial shrinkage due to water evaporation upon gas injection and then generated an expansion due to CO 2 uptake and carbonate precipitation. As carbonation proceeded, the deformation was switched to a secondary shrinkage after expansion. The residual deformation due to carbonation curing was shrinkage in cement paste samples and expansion in concrete samples. This was because the relative expansion due to carbonate precipitation in paste was not large enough to compensate for the shrinkage caused by water loss. However, for concrete samples, the introduction of aggregates reduced the pore spaces in concrete, leading to an expansion owing to the limited precipitation. The results of carbon dioxide uptake, XRD, and SEM analysis confirmed that calcium carbonate formation played a critical role in the relative expansion. The study also showed that cement-based products were more resistant to weathering carbonation after the early-age carbonation curing. After 61-day weathering carbonation exposure, both paste and concrete samples exhibited carbonation shrinkage as a result of carbonation of hydration products. However, the magnitude of shrinkage was much smaller in carbonation curing than in weathering carbonation because of the short period of exposure. Both carbonations did not significantly affect the compressive strength of carbonated products. Carbonation curing likely makes concrete products more dimensionally stable in the long-term service.